2016
DOI: 10.1016/j.carbpol.2015.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, analysis and antioxidant evaluation of the controlled product of polysaccharide from Mactra veneriformis by mild acid hydrolysis

Abstract: The polysaccharides from Mactra veneriformis (MVPS) were degraded by controlled mild acid hydrolysis to produce active oligosaccharides. MVPS can easily be hydrolyzed by H2SO4 or HCl. The hydrolyzing process was investigated in acid addition and reaction time by evaluating the producing content of reducing sugar. Hydrolysis with 1M HCl to MVPS can generate a time-depended behavior that is mild and controllable. HPLC analysis monitored the change of oligosaccharides composition in hydrolyzing. Total nine oligos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In our previous research (Wang et al, 2016), we degraded MVPS by mild H 2 SO 4 or HCl hydrolysis and found that hydrolysates were extremely influenced by adding an amount of acid and by the reaction time. To avoid thorough hydrolysis and obtain more oligosaccharide content in the product, degradation with 0.5 h of HCl was adopted to process MVPS due to its controllability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous research (Wang et al, 2016), we degraded MVPS by mild H 2 SO 4 or HCl hydrolysis and found that hydrolysates were extremely influenced by adding an amount of acid and by the reaction time. To avoid thorough hydrolysis and obtain more oligosaccharide content in the product, degradation with 0.5 h of HCl was adopted to process MVPS due to its controllability.…”
Section: Discussionmentioning
confidence: 99%
“…The product Ah-MVPS were correspondingly prepared by incomplete degradation of HCl, as reported in our previous study (Wang et al, 2016). In brief, about 2.0g MVPS was dissolved in 100 mL distilled water to prepare 20 mg/mL of solution.…”
Section: Preparation Of Ah-mvpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with their initial polysaccharides, the produced low molecular mass fragment exhibited increasing bioactivities because of their higher bioavailability and easier absorbency in living organisms (Juśkiewicza, Zduńczyk, Jankowski, Król, & Milala, 2008). Moreover, the derived oligosaccharides might produce some novel physiological activity owing to their different physicochemical properties and molecular structures (Moura, Macagnan, & Silva, 2015; Wang, Wu, Ji, Xue, & Liu, 2016). But up to present, few researchers have focused on hydrolysis of PPe and the anti‐oxidative stress effect on their degrading products.…”
Section: Introductionmentioning
confidence: 99%
“…The biological and physicochemical properties of biomacromolecules are different from those of conventional drug substances, particularly with regard to their molecular weight, physicochemical stability, solubility, biological half-life, conformational stability, oral bioavailability, dose requirements, and administration (Wang et al, 2009;Xiong, 2016). Natural polysaccharides exhibiting their biological activities are concerned with the oligosaccharide derivatives that are produced by gastric acid or gastric enzymes in the digestive tract (Agbagla-Dohnani et al, 2012;Wang et al, 2016). Several studies in recent years have shown that the derived oligosaccharides produced by the acid or enzymatic hydrolysis of polysaccharides can be used as antioxidants or prebiotics (Daisy et al, 2015;Suphavadee et al, 2016;Xu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%